Manajamen Pemeliharaan dan Pemberian Pakan Ternak Sapi Potong Di Desa Sebewe Kecamatan Moyo Utara Kabupaten Sumbawa - Mietra Anggara; Imam Munandar; Silvia Firda Utami; Fadhli Dzril Ikram; M. Faisal (JASTEN (Jurnal Aplikasi Sains Teknologi Nasional), 2022)
Feed is all that can be eaten by livestock, both in the form of organic and inorganic materials, which can be partially or completely digested and does not interfere with health. Good feed is feed that contains quality food substances, such as energy, protein, fat, minerals and vitamins, to produce high-quality and high-quantity meat products. 70% of production costs are spent on feed. Therefore, assistance and training are needed so that the use of feed is efficient and meets the nutritional needs of livestock. The activity was carried out on August 4, 2020, located in the Sebewe Village, Moyo Utara District, Sumbawa Regency, West Nusa Tenggara Province. The activity method is in the form of Problem-Solution and Demo directly to the community. This activity began with the delivery of material on livestock rearing management (mating management), weaning management, management of feeding and care, then continued with activities giving material on cattle feed formulations, demos of making cattle feed and operation and maintenance of animal feed machines (concentrates). The conclusion from this activity is that farmers in Sebewe Village, Moyo Utara District, have not implemented good feeding management for beef cattle and concentrated feed for livestock. This is due to the lack of knowledge and understanding of the community about good management of maintenance and feeding of beef cattle.